TAS-102: a novel antimetabolite for the 21st century. (January 2016) - Uboha, Nataliya; Hochster, Howard S
TAS-102, a novel antimetabolite combination chemotherapy agent, consists of a rediscovered antimetabolite agent, trifluorothymidine (trifluridine) combined with the metabolic inhibitor of thymidine phosphorylase, tipiracil, in a 1:0.5 molar ratio. Mechanism of action studies suggest that this agent works by incorporation into DNA. Both preclinical and clinical studies demonstrate that this agent is noncross-resistant with 5-fluorouracil. Tipiracil may also have antiangiogenic effects through inhibition of thymidine phosphorylase. Recent randomized Phase II and III trials demonstrate clinical activity (improved progression-free survival, time to decrease in performance status, prolonged overall survival) in metastatic colorectal cancer refractory to all standard agents. Monotherapy with TAS-102 has now been approved for this indication in Japan and in the USA.